2009
DOI: 10.1177/0192623308329285
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Hepatic Mitochondrial Injury Induced by Fatty Acid Oxidation Inhibitors

Abstract: Impairment of liver mitochondrial β-oxidation is an important mechanism of drug-induced liver injury. Four inhibitors of fatty acid oxidation were compared in short-term rat in vivo studies in which the rats were administered one or four doses. The hepatocellular vacuolation represented ultrastructural mitochondrial changes. Urine nuclear magnetic resonance (NMR) spectroscopy revealed that both FOX988 and SDZ51-641 induced a persistent dicarboxylic aciduria, suggesting an inhibition of mitochondrial β-oxidatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
45
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 54 publications
2
45
0
1
Order By: Relevance
“…Although direct perturbations to the mitochondrial membrane by inhibition of FAO - via accumulation of ceramide (14,33) or free fatty acids (44) - could be a proposed mechanism for the observed effects, our data suggest that EX does not lead to ceramide or long-chain fatty acyl-CoA accumulation in leukemia cells. Alternatively, it is conceivable that inhibition of mitochondrial FAO may result in increased generation of toxic dicarboxylic acids via microsomal ω-oxidation of excess fatty acids (45). Nevertheless, the synergism between orlistat (which does not promote ceramide or palmitate accumulation) and ABT-737 or Nutlin 3a motivates us to contemplate the possibility that fatty acid entry and/or FAO in mitochondria may ipso facto be involved in the regulation of the Bcl-2 apoptotic rheostat in leukemia cells.…”
Section: Discussionmentioning
confidence: 99%
“…Although direct perturbations to the mitochondrial membrane by inhibition of FAO - via accumulation of ceramide (14,33) or free fatty acids (44) - could be a proposed mechanism for the observed effects, our data suggest that EX does not lead to ceramide or long-chain fatty acyl-CoA accumulation in leukemia cells. Alternatively, it is conceivable that inhibition of mitochondrial FAO may result in increased generation of toxic dicarboxylic acids via microsomal ω-oxidation of excess fatty acids (45). Nevertheless, the synergism between orlistat (which does not promote ceramide or palmitate accumulation) and ABT-737 or Nutlin 3a motivates us to contemplate the possibility that fatty acid entry and/or FAO in mitochondria may ipso facto be involved in the regulation of the Bcl-2 apoptotic rheostat in leukemia cells.…”
Section: Discussionmentioning
confidence: 99%
“…8) When NAFLD occurs, excess FFAs in the liver cells lead to the development of lipid peroxidation and the generation of a large number of ROS, which are the major indicators of oxidative stress. 43) Consequently, ROS prompt the generation of TNF-α, which inhibits mitochondria respiration and induces and aggravates insulin resistance. 44,45) Superoxide dismutase (SOD) is an important antioxidant enzyme and the primary means of free radicals scavenging in organisms.…”
Section: Discussionmentioning
confidence: 99%
“…Cytoplasmic vacuolation was also observed in some hepatocytes, which strongly suggest the presence of ultrastructural changes include deposition of fat droplets (Watanabe and Yanagita, 1983), excess accumulation of glycogen (Nayak et al, 1996), mitochondrial changes (Vickers, 2009), and multiple vacuoles with poor cytoplasmic architecture (Adewole and Ojewole, 2007). Our findings concerning increasing values of AST, ALT and LDH, as well as appearance of necrosis caused by acetone treatment are in agreement with those of other authors who showed that, the appearance of necrosis with vacuolation seemed to be associated with increased levels of hepatic biomarkers such as ALT, AST and LDH (Shimada et al, 2015).…”
Section: Discussionmentioning
confidence: 99%